RESPON ANATOMIS AKAR DAN PERTUMBUHAN TANAMAN PADI (Oryza sativa L.) KULTIVAR IR64 DAN INPARA 5 TERHADAP TINGGI DAN LAMA GENANGAN - , FITRI RAHAYU ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Rice (Oryza sativa L.) is the most important crop commodity in Indonesia. Environment factor such as global climate is one of barrier rice productivity in Indonesia. Water has defined as a factor for growth and productivity on rice. The purpose of this study was to analize the anatomical and growth respones of rice (Oryza sativa L.) variety Inpara 5 and IR64 on different of height and period of submergence. The research was carried out in greenhouse of Faculty of Biology University Gadjah Mada and Laboratory of Plant Structure and Development. The research was conducted with Completed Randomized Design (CRD) type factorial on height treatment (plant lenght 0 cm/T0, half plant flooded/TÂ½, and completed plant flooded/T1) and period (5 days flooding/L5, 10 days flooding/L10, and 15 days flooding/L15) submergence. Seeds were germinated and grown for 14 days in polybag, then submergence treatment was applied. Physiological characters measured were plants height, total leaves number, and shoot-root ratio. Results showed that the height and period submergence treatment increased roots diameter, cortex thickness, aerenchyma diameter, and root pith diameter of rice (Oryza sativa L.) cultivar IR64 and Inpara 5. Submergence treatment increased plants height, total leaves number, and shoot-root ratio on rice IR64 (Oryza sativa L. cv. IR64). Period submergence increased plants height, total leaves number, and shoot-root ratio on rice Inpara 5 and height treatment decreased plants height, total leave numbers, and shoot-root ratio on rice Inpara 5 (Oryza sativa L. cv. Inpara 5).